DAMPAK COVID-19 TERHADAP PELAKSANAAN PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH NAGARI BINJAI - Lutfi, Mutia (Najah Bestari, 2023)
The aim of this research is to find out the impact of Covid-19 on the implentation of Arabic language learning at MTSS Nagari Binjai. This type of research uses qualitative research with descriptive methods. The data collection technique is through observation, interview and dokumentation. This resaerch shows that the pandemic on the implementation of Arabic language learning for MTSS Nagari Binjai students, especially in class VII, has had both negative and positive impacts. This shows how students interact in learning. Here it is explained that there are negative and also positive impacts on the implementation of arabic language learning. First, here we will explain the negative impacts, namely first, student concentration decreases during the learning process. Second, student responses when learning are very poor. And finally, students lack of self-confidence. Students are more busy with their cellphones than studying. The positive impacts are first, it is very easy to access material and information. Second, creating a good atmoshere and cooperation. There is support of parents in the learning process.